1993
DOI: 10.1017/cbo9780511565595
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Regulation in Laboratory Rodents

Abstract: Rodents are the predominant experimental animals found in life-sciences research laboratories. The body temperature of a rodent is markedly affected by surgical, chemical or environmental manipulation. Because temperature regulation is controlled essentially by a 'holistic' regulatory system, meaning that its responses affect the activities of all other psychological and behavioural processes, it is clear that researchers working with rodents must be familiar with thermoregulatory physiology. With the help of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
389
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(405 citation statements)
references
References 0 publications
10
389
0
6
Order By: Relevance
“…Although we found that motor activity was a positive predictor of body temperature, which is consistent with many previous studies (Gordon, 1993;Gordon and Yang, 1997;Kent et al, 1991;Re®netti, 1994), this result does not necessarily imply that wheel running caused an increase in body temperature (Gordon and Yang, 1997). For example, body temperature may have been elevated in anticipation of motor activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although we found that motor activity was a positive predictor of body temperature, which is consistent with many previous studies (Gordon, 1993;Gordon and Yang, 1997;Kent et al, 1991;Re®netti, 1994), this result does not necessarily imply that wheel running caused an increase in body temperature (Gordon and Yang, 1997). For example, body temperature may have been elevated in anticipation of motor activity.…”
Section: Discussionsupporting
confidence: 87%
“…Under normothermic conditions, body temperatures of house mice range from 34 to 398C (Gordon, 1993). Such variation has multiple causes.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologists have found major differences between the thermal physiology of mice, other mammals, and humans [3,[5][6][7][8][9][10][11][12], such that at ambient temperatures in which humans feel comfortable, mice experience chronic mild cold stress directly impacting their metabolism and thermoregulatory status. Laboratory mice are almost always housed and studied at mildly cool temperatures well below their 'thermoneutral zone' which is the ambient temperature in which metabolic heat production is minimal and the mouse does not need to work to keep warm or cold.…”
Section: Room Temperature: So Much More Than a Thermometer Readingmentioning
confidence: 99%
“…Housing mice at, or just below, standard housing temperatures has been shown to decrease reproduction 8,9 , growth 10,11 , organ weight 10 , immune function 10 and increase metabolic rate [12][13][14] . Increasing laboratory ambient temperatures is not a solution because mice prefer different temperatures for different behaviors, times of day and between genders [15][16][17][18] .…”
Section: Temperature As An Example Of Environmental Stressmentioning
confidence: 99%
“…Barnett 45 documented wild house mice living and breeding in food storage freezers, which were kept at − 10 °C. However, studies of hypothermia show that mice can no longer right themselves after 30-99-min exposure at a similar temperature 14 . The difference between the two scenarios is that wild mice in the freezer were able to build an insulating nest, which likely reduced heat loss and created a more favorable thermal microclimate 45 .…”
Section: Thermal Stress and Its Effect On Mouse Modelsmentioning
confidence: 99%